The effectiveness of homeopathy in the treatment of the most common health problems - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
On July 5, the Ministry of Health of Ukraine published a news about the ineffectiveness of homeopathy, referring to the results of the Australian study. This is a brief overview of these results.